2021
DOI: 10.1002/mc.23374
|View full text |Cite
|
Sign up to set email alerts
|

NUAK family kinase 2 is a novel therapeutic target for prostate cancer

Abstract: Current advancements in prostate cancer (PC) therapies have been successful in slowing PC progression and increasing life expectancy; however, there is still no curative treatment for advanced metastatic castration resistant PC (mCRPC). Most treatment options target the androgen receptor, to which many PCs eventually develop resistance. Thus, there is a dire need to identify and validate new molecular targets for treating PC. We found NUAK family kinase 2 (NUAK2) expression is elevated in PC and mCRPC versus n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“… 24 While recent studies have shown that NUAK2’s critical roles in liver and prostate cancers, its specific function in pancreatic cancer has remained unclear. 38 , 39 To address this gap, we initiated an investigation into the functional role of NUAK2 in pancreatic cancer cells by employing siRNA to target NUAK2. Our findings showed that NUAK2 knockdown inhibited the proliferation of pancreatic cancer cells, reduced their ability to migrate and invade, and induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 24 While recent studies have shown that NUAK2’s critical roles in liver and prostate cancers, its specific function in pancreatic cancer has remained unclear. 38 , 39 To address this gap, we initiated an investigation into the functional role of NUAK2 in pancreatic cancer cells by employing siRNA to target NUAK2. Our findings showed that NUAK2 knockdown inhibited the proliferation of pancreatic cancer cells, reduced their ability to migrate and invade, and induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…AMP‐related kinases have functions as sensors coupling cellular energy status to cell growth and proliferation. The activation of NUAK2 is speculated to result in cancer development and tumor progression (Fu et al, 2022; Gill et al, 2018; Namiki, Coelho, & Hearing, 2011; Yuan et al, 2018). NUAK2 has functions to phosphorate MYPT1 and to regulate the cytoskeleton, which results in facilitating cell proliferation by fiber maintenance, in addition to having a critical role in YAP‐driven tumorigenesis by regulating both the YAP and Hippo pathways (Gill et al, 2018) and NUAK2 also activates mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the AMPK protein kinase family, acting as a critical sensor coupling cellular energy status to cell growth and proliferation [38]. The deregulation of NUAK2 has profound effects on cancer development and tumor progression, and is seen as a potential therapeutic target for several cancer-related diseases [39,40]. The NUAK2 amino acidic sequence (1-628) is predicted to bear two main disordered regions (355-493; 531-562), with the kinase domain comprising residues 53-303.…”
Section: Kdss ± Sd (M)mentioning
confidence: 99%